Agent oriented methodology for malaria transmission modelling and simulation - Loh, Chee Wyai; Shane, Nissom; Cheah, Wai Shiang; Nurfauza, Jali (Universiti Utara Malaysia, 2017)
Epidemiology study like malaria study is receiving much at-tention among the researchers nowadays. To model the epidemiology study like malaria, one can adopt different equations to formulate the problem. Al-ternatively, individual based modelling is started to emerge and useful for epidemiology study due to the nature of flexibility ad emergence behaviour of individual based modelling. Since various epidemiology mathematical models has been introduced and implemented, can we reuse the models in individual based modelling? In fact, it is possible but not a straightforward process. This paper presents a systematical approach for individual based epidemiology modelling and simulation by reusing the existing mathemati-cal models on epidemiology study. With the systematic approach, a rapidly prototyping of epidemiology study is introduced. Also, it promotes the com-prehensiveness and model transformation across technical and non-technical person.